Mapping of Carbon Dioxide (Co2) Emissions Due To Increased Vehicle Volume in Mataram City - Rifky Bagus Saputra (CV. Syntax Corporation Indonesia, 2023)
The high level of population and activities in the city of Mataram also increases the use of vehicles as a secondary need for the community to help with daily activities in land transportation. As the use of vehicles increases, the demand for fuel oil (BBM) also increases. Fuel is a material that can be converted into energy by burning fuel where the fuel contains heat energy that can be released and manipulated. Vehicle emissions are a major source of pollution in big cities in Indonesia. CO2 is a compound consisting of the elements carbon and oxygen with the writing CO2. Carbon dioxide is a gaseous element that exists at atmospheric temperature and pressure. The hope for this research is to determine CO2 levels in the city of Mataram and prevent CO2 emissions from increasing. The results of calculating the highest vehicle volume are located in segment III Jalan Majapahit of 3506 pcu/hour which occurs at 17:00 - 17:15 WITA. The results of the regression analysis between vehicle volume as the X variable and CO2 gas emissions as the Y variable on the five road segments conducted by the study were y = 134.57 ln(x) - 970.14 with an R2 value of 0.8661 included in the 0.80 interval – 1,000 which means that the strength of the relationship between vehicle volume and CO2 emissions has a very strong relationship and vehicle volume contributes 86.6165% to CO2 emissions. Based on the results of the discussion that was carried out, the CO2 gas emission levels in all road segments carried out had an average CO2 gas emission level value of 103.31 – 108.56 kg/hour.